fix import/export of ierode common on Windows
[scilab.git] / scilab / modules / differential_equations / src / fortran / prja.f
index 6cecbac..d9def4c 100644 (file)
@@ -2,6 +2,9 @@ C/MEMBR ADD NAME=PRJA,SSI=0
       subroutine prja (neq, y, yh, nyh, ewt, ftem, savf, wm, iwm,
      1   f, jac)
 clll. optimize
+      
+      include 'stack.h'
+      
       external f, jac
       integer neq, nyh, iwm
       integer iownd, iowns,
@@ -18,8 +21,6 @@ clll. optimize
      1   vmnorm, fnorm, bnorm
       dimension neq(*), y(*), yh(nyh,*), ewt(*), ftem(*), savf(*),
      1   wm(*), iwm(*)
-      integer         iero
-      common /ierode/ iero
       common /ls0001/ rownd, rowns(209),
      2   ccmax, el0, h, hmin, hmxi, hu, rc, tn, uround,
      3   iownd(14), iowns(6),
@@ -74,7 +75,7 @@ c if miter = 1, call jac and multiply by scalar. -----------------------
       do 110 i = 1,lenp
  110    wm(i+2) = 0.0d+0
       call jac (neq, tn, y, 0, 0, wm(3), n)
-      if(iero.gt.0) return
+      if(ierror.gt.0) return
       con = -hl0
       do 120 i = 1,lenp
  120    wm(i+2) = wm(i+2)*con
@@ -91,7 +92,7 @@ c if miter = 2, make n calls to f to approximate j. --------------------
         y(j) = y(j) + r
         fac = -hl0/r
         call f (neq, tn, y, ftem)
-      if(iero.gt.0) return
+      if(ierror.gt.0) return
         do 220 i = 1,n
  220      wm(i+j1) = (ftem(i) - savf(i))*fac
         y(j) = yj
@@ -122,7 +123,7 @@ c if miter = 4, call jac and multiply by scalar. -----------------------
       do 410 i = 1,lenp
  410    wm(i+2) = 0.0d+0
       call jac (neq, tn, y, ml, mu, wm(ml3), meband)
-      if(iero.gt.0) return
+      if(ierror.gt.0) return
       con = -hl0
       do 420 i = 1,lenp
  420    wm(i+2) = wm(i+2)*con
@@ -144,7 +145,7 @@ c if miter = 5, make mband calls to f to approximate j. ----------------
           r = max(srur*abs(yi),r0/ewt(i))
  530      y(i) = y(i) + r
         call f (neq, tn, y, ftem)
-      if(iero.gt.0) return
+      if(ierror.gt.0) return
         do 550 jj = j,n,mband
           y(jj) = yh(jj,1)
           yjj = y(jj)